214k views
0 votes
Consider the equation 3p - 7 + p = 13. What is the resulting equation after the first step in the solution?

Op-7 = 13-3p
O 2p-7 = 13
O 3p-7 = 13-
4p - 7 = 13

User DimonZa
by
4.9k points

1 Answer

4 votes

Answer:

4p - 7

General Formulas and Concepts:

Pre-Alg

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define

3p - 7 + p = 13

Step 2: Solve for p

  1. Combine like terms: 4p - 7 = 13
  2. Add 7 to both sides: 4p = 20
  3. Divide 4 on both sides: p = 5
User Bryan Ash
by
4.4k points